Analysis of Quality of Life, Depression, and Sexual Function in Patients on the Liver Transplant List - Fidan, Cihan; Akdur, Aydıncan; Kırnap, Mahir; Selçuk, Haldun; Yıldırım, Sedat; Moray, Gökhan; Haberal, Mehmet (Turkish Journal of Gastroenterology, 2021)
Background: The only treatment in patients developing liver failure is liver transplantation. According to the Ministry of Health, thenumber of patients waiting for a liver transplantation is 2141, the average waiting period for liver transplantation is approximately5 years, and 15-18% of these patients lose their life while waiting for transplantation. In these patients, limitations in daily activities anddepression–anxiety are commonly found. The aim of this study was to analyze life quality, depression symptoms, and existence of sexualfunctional disorders of patients waiting for liver transplantation.Methods: A total of 74 patients, who were registered in Başkent University Hospital between 2015 and 2018, were included into thestudy. Short Form-36, Beck Depression Inventory, and Arizona Sexual Experiences Scale were applied to 56 patients who approvedstudy.Results: Most of the patients were male (64.3%), and the mean age was 46 (18-64). Short Form-36 scores were low in all patients. Themean Beck Depression Inventory score of patients was found as 18.4 ± 11.3, and they were suffering from moderate depressive symptoms.According to Arizona Sexual Experiences Scale, total mean scores of males was found as 16.3 ± 5.5, and for females, it was 19.5 ±5.3 with a statistically significant difference (P < .05). It was found that sexual dysfunction mostly had moderate to mild.Conclusion: Depression and sexual dysfunction are common in patients with chronic liver diseases, and their life qualities deterioratesignificantly. It is anticipated that evaluation of these patients in terms of psychological issues and sexual dysfunction will increase theirquality of life during the organ waiting period and affect their well-being post-transplant.